Assessment Of The Clinical Treatment Outcomes And Direct Medical Costs Among Type 2 Diabetes Mellitus Outpatients At The Hospital Universiti Sains Malaysia - Abougalambou, Salwa Selim Ibrahim (2011)
Diabetes mellitus (DM) is becoming a major public health problem, especially now that a large proportion of health care expenditure is being spent on the treatment of this disease and its complications. This was a prospective observational study of diabetes type 2 patients with the objectives of assessing the treatment modalities, glycaemic control and the factors associated with the development of macro and microvascular complications, and evaluating the direct medical costs of treating diabetic type 2 patients at the Hospital Universiti Sains Malaysia (HUSM). All of the type 2 diabetes patients who attended and were followed-up at the HUSM diabetes clinic were included in this study.